2005
DOI: 10.1111/j.1365-2907.2005.00053.x
|View full text |Cite
|
Sign up to set email alerts
|

The response of mammals to forest fire and timber harvest in the North American boreal forest

Abstract: 1. This paper reviews and compares the effects of forest fire and timber harvest on mammalian abundance and diversity, throughout successional time in the boreal forest of North America. 2. Temporal trends in mammal abundance and diversity are generally similar for both harvested and burned stands, with some differences occurring in the initiation stage (0-10 years post disturbance). 3. Small mammals and ungulates are most abundant immediately post disturbance, and decrease as stands age. Lynxes and hares util… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
231
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(255 citation statements)
references
References 148 publications
14
231
3
2
Order By: Relevance
“…However, to the best of our knowledge, there is no such work for small mammals. While in Northern America, there were several reviews on effects of forest management on this important group (Kirkland 1990;Fisher and Wilkinson 2005;Zwolak 2009), similar syntheses on European small mammals are still lacking. In this paper, we aimed to summarize the results of studies investigating the influence of forest harvest on small mammal abundance on the stand level.…”
Section: Introductionmentioning
confidence: 99%
“…However, to the best of our knowledge, there is no such work for small mammals. While in Northern America, there were several reviews on effects of forest management on this important group (Kirkland 1990;Fisher and Wilkinson 2005;Zwolak 2009), similar syntheses on European small mammals are still lacking. In this paper, we aimed to summarize the results of studies investigating the influence of forest harvest on small mammal abundance on the stand level.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative reviews of the effects of fire on birds across and within regions (Kotliar et al 2002, Saab andPowell 2005), effects of fuels reduction treatments on vertebrates (Pilliod et al 2006), effects of fire on mammals in boreal forests (Fisher and Wilkinson 2005), and response of herpetofauna to prescribed fire (Russell et al 1999) exist, as well as formal meta-analysis of the effects of thinning on birds (Vanderwel et al 2007) and of wildfire and logging on some smallmammal species (Zwolak 2009). To date, most reviews have relied on qualitative comparisons, employing a vote-counting approach (Rosenberg et al 2000) to the literature and making little formal assessment of the effect size of fire severities, fire surrogates, and time since fire on fauna.…”
Section: Introductionmentioning
confidence: 99%
“…A series of different microhabitats may be created following successive wildfires, depending on the time passed since the previous fire, probably through the selection of different mammal species (Fox 1982, Briani et al 2004, Vieira 1999. In any case, the small mammal assemblage may differ considerably between successional stages (Krefting & Ahlgren 1974, Torre & Diáz 2004, Fisher & Wilkinson 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in nontropical ecosystems, including deserts, grasslands, and temperate forests have recorded a decrease in the abundance of some species immediately after a wildfire (Quinn 1979, Fox 1982, Ojeda 1989, Fa and Sanchez-Cordero 1993, Churchfield 1997, Simon et al 2002, Converse et al 2006, reduced abundance in areas that are burned regularly (Sherburne-Junior 1959, Rana 1985 or the dominance of a few species in burned areas (Krefting & Ahlgren 1974, Kern 1981, Clark & Kaufman 1990. In most cases, the time elapsed since the disturbance seems to be an important variable determining the composition of the mammalian community (Vieira & Marinho-Filho 1998, Ford et al 1999, Simon et al 2002, Torre & Diáz 2004, Fisher & Wilkinson 2005. In the Cerrado, Briani et al (2004) and Vieira (1999) found that small mammals were relatively tolerant to such impacts, and were especially abundant during the early successional stages.…”
Section: Introductionmentioning
confidence: 99%